Understanding College Teachers’ Perception of the Inclusion Policy in Nepal - Limbu, Lila Prasad (Tribhuvan University Journal, 2025)
The Nepalese government adopted an inclusion policy to provide social justice for all. However, the implementation of this policy has created a conflicting situation in the country. This study critically analyzes how social inclusion policies are perceived by college teachers in Nepal, highlighting important obstacles arising from opposing political ideologies and stakeholder interests. The research employs qualitative methods to explore these perceptions. The main aim of this study is to examine information sources of the inclusion policy for making perception, how these sources relate to respondents’ perspectives, and identify the key elements influencing respondents’ perceptions. Much of the information provided to teachers is based on subjective experiences rather than rational truths. Furthermore, respondents’ opinions on the inclusion policy differed greatly depending on their background, expertise, and engagement with public commission services. Some indigenous and non-indigenous people contribute to these misframing social inclusion policy for their own socio and economic benefit, which identifies policy misframing as the result of economic, social, and political opportunities. In the end it recommends better communication and cooperation between government agencies, indigenous organizations, and non-indigenous stakeholders in order to improve comprehension and promote the more successful execution of social inclusion policy throughout Nepal.